Morphological and taxonomic studies on the males of three species of the genus Pseudococcus (Hemiptera: Coccoidea) - Giliomee, J. H (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 1961.